Band engineering of modified rhombohedral Cu4Mn2Te4: ab initio approach. Issue 13 (3rd July 2022) - Priyadharshini, S.; Sundareswari, M.; Viswanathan, E.; Jayalakshmi, D. S.; Manjula, M.
ABSTRACT: Systematic band structure calculations are reported for the first time on the 'modified rhombo (R-3 m) structured Cu4 Mn2 Te4 ' compound by adapting the Lotgering model. Wyckoff positions of all the atoms are estimated. There is a good agreement between the present computed lattice parameter values with the already reported. Mechanism of phase transition from Fd-3m structure (3Cu added spinel CuMn2 Te4 ) to R-3m structure (distorted rhombo Cu4 Mn2 Te4 ) at room temperature is discussed. Spin-polarised calculations reveal Cu4 Mn2 Te4 energetically prefers the AFM phase at ambient conditions. Band structures predict the compound to be of metallic nature at its NM and FM phases whereas a band gap opening occurs at its AFM phase. Band gap value is estimated as ∼ 0.2 eV and ∼0.7 eV using GGA and mBJ exchange–correlation schemes, respectively. Origin of band gap opening is discussed. Total spin magnetic moment ( µB ) per formula unit of Cu4 Mn2 Te4 compound is calculated as 9.878 and −5.001, respectively, at FM and AFM phases. Electrical conductivity is enhanced by a factor of 10 2 from 100 K to 300 K at minority spin states. Maximum optical conductivity occurs at 6500 Ω −1 cm −1 which lies in the visible region of the electromagnetic spectrum.